Pelatihan Penyusunan Desain Pembelajaran Online Multiplatform bagi Guru Madrasah Ibtidaiyah Kelas Atas pada Masa Pandemi Covid-19 - Amelia, Rizki; Islamy, Muhammad Irfan (JRCE (Journal of Research on Community Engagement), 2022)
The Covid-19 pandemic has led to the emergence of various complex problems for educational institutions. The learning process which originally ran face-to-face in the classroom, had to be shifted to face-to-face online or what is known as Distance Learning (PJJ). Distance Learning (PJJ) is a relatively new thing for the education system in Indonesia, including for teachers, students, and parents. The results of various studies show that several obstacles often arise in the implementation of PJJ. Based on the results of the questionnaire, madrasah Ibtidaiyah teachers in East Java experienced confusion in designing effective online learning. Thus, this activity aims to provide training Preparation of Multiplatform Online Learning Designs for Upper Class Madrasah Ibtidaiyah Teachers during the Covid-19 Pandemic Period. This activity takes place through three stages, namely the Preparation Stage, the Implementation Stage and the Report Preparation Stage. The teacher's response to the online learning design preparation training was also very good. A total of 97.7% stated that the use of various online platforms in the lesson plans was very clear. In addition, 94.8% stated that the learning evaluation in this multi-platform online learning design was very interesting and clear, and 96.1% of participants also stated that the online learning design provided during this training was in accordance with what they had hoped for so far and could provide enlightenment in the online learning process during this covid-19 pandemic.